Respuesta :
(x − 7)^2 = x^2 − 14x + 49
using (a-b)^2 = a^2 - 2ab + b^2
answer is A) x^2 − 14x + 49
using (a-b)^2 = a^2 - 2ab + b^2
answer is A) x^2 − 14x + 49
Answer: The correct option is (A) [tex]x^2-14x+49.[/tex]
Step-by-step explanation: We are given to find the following product :
[tex]P=(x-7)^2~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~(i)[/tex]
We will be using the following formula :
[tex](a-b)^2=a^2-2ab+b^2.[/tex]
From (i), we get
[tex]P\\\\=(x-7)^2\\\\=x^2-2\times x\times7+7^2\\\\=x^2-14x+49.[/tex]
Thus, the required product is [tex]x^2-14x+49.[/tex]
Option (A) is CORRECT.